Pharmacologic Inhibition of Histone Deacetylase 6 Prevents the Progression of Chlorhexidine Gluconate-Induced Peritoneal Fibrosis by Blockade of M2 Macrophage Polarization - Shi, Yingfeng; Li, Jinqing; Chen, Hui; Hu, Yan; Tang, Lunxian; Zhou, Xun; Tao, Min; Lv, Zexin; Chen, Si; Qiu, Andong; Liu, Na (Frontiers in Immunology, 2022)
Peritoneal fibrosis contributes to ultrafiltration failure in peritoneal dialysis (PD) patients and thus restricts the wide application of PD in clinic. Recently we have demonstrated that histone deacetylase 6 (HDAC6) is critically implicated in high glucose peritoneal dialysis fluid (HG-PDF) induced peritoneal fibrosis, however, the precise mechanisms of HDAC6 in peritoneal fibrosis have not been elucidated. Here, we focused on the role and mechanisms of HDAC6 in chlorhexidine gluconate (CG) induced peritoneal fibrosis and discussed the mechanisms involved. We found Tubastatin A (TA), a selective inhibitor of HDAC6, significantly prevented the progression of peritoneal fibrosis, as characterized by reduction of epithelial-mesenchymal transition (EMT) and extracellular matrix (ECM) protein deposition. Inhibition of HDAC6 remarkably suppressed the expression of matrix metalloproteinases-2 (MMP2) and MMP-9. Administration of TA also increased the expression of acetylation Histone H3 and acetylation α-tubulin. Moreover, our results revealed that blockade of HDAC6 inhibited alternatively M2 macrophages polarization by suppressing the activation of TGF-β/Smad3, PI3K/AKT, and STAT3, STAT6 pathways. To give a better understanding of the mechanisms, we further established two cell injured models in Raw264.7 cells by using IL-4 and HG-PDF. Our in vitro experiments illustrated that both IL-4 and HG-PDF could induce M2 macrophage polarization, as demonstrated by upregulation of CD163 and Arginase-1. Inhibition of HDAC6 by TA significantly abrogated M2 macrophage polarization dose-dependently by suppressing TGF-β/Smad, IL4/STAT6, and PI3K/AKT signaling pathways. Collectively, our study revealed that blockade of HDAC6 by TA could suppress the progression of CG-induced peritoneal fibrosis by blockade of M2 macrophage polarization. Thus, HDAC6 may be a promising target in peritoneal fibrosis treatment.